Capital markets and valuation models of investment properties. A pre and post crisis analysis - María Paz Horno-Bueno; Ana Licerán-Gutiérrez; Rafael Bautista-Mesa (Revista de Contabilidad: Spanish Accounting Review, 2022)
This work analyses the effect of the fair value and historical cost models, optionally applicable under IAS 40 for investment properties on the market value of Spanish groups of real estate listed companies between 2005 and 2018. The results of the application of the Ohlson Model do not suggest any relationship of financial information with the market value in the pre-crisis and economic crisis periods. However, in the post-crisis period, financial information represented by book value gains relevance, showing a significant positive relationship with the market value of real estate companies, although suggesting a reduction in the asymmetry of financial information in companies using the fair value method.